International programs for Ukrainian students and academic staff - Панченко, Віолетта Володимирівна; Бельмаз, Ярослава Миколаївна (My University, 2022)
Розглянуто можливості участі в міжнародних проєктах, академічній мобільності, підвищення кваліфікації для науково-педагогічних працівників і здобувачів освіти, які пропонують міжнародні урядові та громадські організації, заклади вищої освіти європейських країн.The publication is devoted to considering the possibilities of participation in international projects, academic mobility, advanced training for academic staff and students offered by international governmental and public organizations, institutions of higher education of European countries.
Панченко В.В. International programs for Ukrainian students and academic staff / В.В. Панченко, Я. М. Бельмаз // Підвищення якості національної освіти у контексті викликів сьогодення : матеріали Регіон. наук.-практ. конф. ( м. Харків, 26 травня 2022 р. ). – Харків : ФОП Петров В. В., 2022. – С. 194-195
Keywords: академічна мобільність, міжнародна співпраця, науково-педагогічні працівники, здобувачі вищої освіти; academic mobility, international cooperation, academic staff, students of higher education institutions